2022
DOI: 10.1111/jonm.13868
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the level of burnout and resilience among hospital based nurse managers after COVID 19 — A cross‐sectional questionnaire‐based study

Abstract: Aim We aim to investigate burnout and resilience among hospital based nurse managers post COVID‐19 in order to suggest appropriate person‐centred leadership support. Background Nurse leaders are central to establishing safe and caring environments for patients and staff. Therefore, their own wellbeing is crucial, particular in times of crisis where they must provide support and guidance. Methods Cross‐sectional questionnaire included ward managers. Data collected were burnout inventory, brief resilience score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…Supervisor nurses and deputy chief nurses have been working on the front line for a long time and their problem-solving skills are still insufficient. In addition, competition for the promotion of professional qualificationsis fierce, putting heavy pressure on the group [ 34 ]. The chief nurse is the highest professional title and there is no pressure for promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Supervisor nurses and deputy chief nurses have been working on the front line for a long time and their problem-solving skills are still insufficient. In addition, competition for the promotion of professional qualificationsis fierce, putting heavy pressure on the group [ 34 ]. The chief nurse is the highest professional title and there is no pressure for promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Forty percent of these leaders reported they were intending to or considering leaving their position; 46% of those intending to leave were doing so at least in part for a better work-life balance and 47% because of burnout and exhaustion. 17 Other studies across the globe have also begun to reveal burnout, 18 moral distress, 19 and experiences of excessive pressures or workload for nurse managers. 14,19 The pandemic's impact on nurses and nurse managers in turn impacts the ability of hospitals and ambulatory clinics to provide high-quality care to patients.…”
Section: The Ongoing Problem Of the Psychosocial Impact On Frontline ...mentioning
confidence: 99%
“…10 The American Organization for Nursing Leadership’s longitudinal study on the impact of COVID-19 on nursing leaders 17 reported in October 2022 that 17% of the 1668 hospital and ambulatory leaders considered themselves “not emotionally healthy,” with 1% reporting they were “not at all emotionally healthy.” Forty percent of these leaders reported they were intending to or considering leaving their position; 46% of those intending to leave were doing so at least in part for a better work-life balance and 47% because of burnout and exhaustion. 17 Other studies across the globe have also begun to reveal burnout, 18 moral distress, 19 and experiences of excessive pressures or workload for nurse managers. 14,19…”
Section: The Ongoing Problem Of the Psychosocial Impact On Frontline ...mentioning
confidence: 99%
“…Previous nursing studies have used a variant‐centered approach, testing the relationship between nurses' psychological resilience and other variables (Pallesen et al, 2022). The variable‐centered approach typically involves categorizing subjects based on the scales' total or mean scores and then examining variables' correlations.…”
Section: Introductionmentioning
confidence: 99%